Antiphospholipid Antibodies in Sickle Cell Disease: A Systematic Review and Exploratory Meta-Analysis. (31st March 2021) - Merashli, Mira; Arcaro, Alessia; Graf, Maria; Caruso, Matilde; Ames, Paul R. J.; Gentile, Fabrizio
The relationship between antiphospholipid antibodies (aPL) and sickle cell disease (SCD) has never been systematically addressed. Our aim was to evaluate potential links between SCD and aPL in all age groups. EMBASE/PubMed was screened from inception to May 2020 and Peto odds ratios for rare events were calculated. The pooled prevalence (PP) of IgG anticardiolipin antibodies (aCL) was higher in individuals with SCD than in controls (27.9% vs 8.7%, P < 0.0001), that of IgM aCL was similar in the two groups (2.9% vs 2.7%); only individuals with SCD were positive for lupus anticoagulant (LA) (7.7% vs 0%, P < 0.0001). The PP of leg ulcers was similar between aPL positive and negative individuals (44% vs 53%) and between patients in acute crisis and stable patients (5.6% vs 7.3%). Reporting of aPL as a binary outcome and not as a titer precluded further interpretation. The results indicate that a prospective case-control study with serial measurements of a panel of aPL in SCD patients might be warranted, in order to understand further the possible pathogenic role of aPL in SCD.